2014
DOI: 10.1177/0009922814521285
|View full text |Cite
|
Sign up to set email alerts
|

Development of a 5-Item Parent Questionnaire to Screen Preschool Children for Reading Problems

Abstract: A very brief parent questionnaire may be useful as a first-line screener for early reading problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…In a previously published study, we described the development and validation of a 5-item parent questionnaire to screen preschool children for later reading problems. 15,16 We also showed that use of general developmental screeners, such as the Ages and Stages Questionnaire and the Survey of Well Being in Young Children, miss preschool children who have a delay in ELS. 17 In our sample, parents of 51% of the children who passed the Ages and Stages Questionnaire and 39% of those who passed the Survey of Well Being in Young Children had concerns about their child's ELS.…”
Section: T a G G E D P What's Newmentioning
confidence: 85%
“…In a previously published study, we described the development and validation of a 5-item parent questionnaire to screen preschool children for later reading problems. 15,16 We also showed that use of general developmental screeners, such as the Ages and Stages Questionnaire and the Survey of Well Being in Young Children, miss preschool children who have a delay in ELS. 17 In our sample, parents of 51% of the children who passed the Ages and Stages Questionnaire and 39% of those who passed the Survey of Well Being in Young Children had concerns about their child's ELS.…”
Section: T a G G E D P What's Newmentioning
confidence: 85%
“…However, the ELS has been validated using the Get Ready to Read Revised as the reference measure. 13,17 The current study was limited to a high-risk, low-income population. Therefore, our findings may not generalize to other settings or subpopulations.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Screening for delays in literacy development was done using the Early Literacy Screener (ELS), a brief 5-item parent questionnaire, previously developed and validated by members of our team. 13 The characteristics of the different screening tools are detailed in Tables 1 and 2.…”
Section: Screening Toolsmentioning
confidence: 99%
“…Score of 7 or higher on 5-question version of the GRTR-R screener 24 The GRTR-R is administered verbally by nurses or medical assistants at the 4-y well visit, responses were recorded in the EHR, and summary scores were automatically calculated within the EHR. Social-emotional well-being…”
Section: Meeting Literacy Milestonesmentioning
confidence: 99%